Selective Laser Melted Titanium Alloy for Transgingival Components: Influence of Surface Condition on Fibroblast Cell Behavior. Issue 1 (3rd March 2021) - Crenn, Marie‐Joséphine; Benoit, Aurélie; Rohman, Géraldine; Guilbert, Thomas; Fromentin, Olivier; Attal, Jean‐Pierre; Bardet, Claire
Abstract: Purpose: To mechanically characterize and assess the biological properties of Ti6Al4V surfaces obtained by Selective Laser Melting in order to determine whether this process is conceivable for production of implant‐supported prostheses and particularly trans‐gingival components. As‐built and polished surfaces were studied in comparison with components obtained by computer numerical control machining technology in order to consider whether the properties are in the same range as the conventional method currently used. Materials and Methods: Cylindrical specimens of Ti6Al4V (n = 6) were built with Selective Laser Melting for the characterization of mechanical properties according to ISO 22674 and discs (n = 12) were fabricated in the same conditions for cytotoxicity evaluation. Discs (n = 12) of Ti6Al4V were also obtained by computer numerical control machining as control. Half of the number of discs (n = 6) from each process were polished, to simulate the laboratory protocol for polishing of transmucosal components and half of the discs remained unaltered (as‐built). Surface roughness measurements of disc specimens (as‐built and polished) were compared with computer numerical control milling specimens (as‐built and polished). Proliferation of human gingival fibroblasts on Ti6Al4V surfaces was also assessed for each condition. Viability and cell morphology were then evaluated qualitatively. Ra and Sa data were compared using Student's t‐test (α = 0.05) and metabolic activity data were compared using Kruskal‐Wallis statistical test (α = 0.05). Results: Selective Laser Melting specimens showed elongation at break greater than 2% and 0.2% yield strength better than 500MPa which complied with ISO 22674 standards. Although Selective Laser Melting samples displayed significantly increased roughness on as‐built surfaces compared to computer numerically controlled milling samples ( p < 0.05), no statistically significant difference was observed after mechanical polishing ( p = 0.279). Regarding metabolic activity, no statistical difference was observed between groups at day 3 ( p > 0.05) and fibroblasts showed a viability higher than 97% on all discs. Cell shapes on polished samples suggested moderate adhesion compared to unpolished samples. Conclusion: With the manufacturing parameters selected in this study, Selective Laser Melting of Ti6Al4V appeared to be compatible with a prosthetic application type 4 according to ISO 22674. Surfaces obtained, followed by recommended postprocessing provided components with equivalent biological properties compared to computer numerical control machining technology.